1993
DOI: 10.1176/ajp.150.4.595
|View full text |Cite
|
Sign up to set email alerts
|

Separation anxiety in panic disorder

Abstract: The hypothesis that separation anxiety is a prevalent affective undercurrent in the dreams and screen memories of panic disorder patients was supported. Significantly higher covert hostility in the panic disorder patients' dreams may support Bowlby's observation that people with high separation anxiety tend to disavow their anger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Previous research has shown that anxiety disorders directly influence, affect, and alter dreams and dream contents of clinical patients diagnosed with such disorders (Desroches & Kaiman, 1964; Foss, 1994; Free et al, 1993; Gentil & Lader, 1978; Khodarahimi, 2009; Kirschner, 1999; Miller et al, 2015; Nadorff et al, 2014; Simon et al, 2016; Swart et al, 2013). In terms of the influence of anxiety disorders on dreams and dream characteristics, it might be assumed that the presence of a clinical anxiety disorder may lead to more frequent and more intense, fearful, frightening, and harming dreams, instigate anxiety-related feelings, thoughts, or emotions in dreams and may also enhance nightmare frequency, as well as increase subjective distress from nightmares.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that anxiety disorders directly influence, affect, and alter dreams and dream contents of clinical patients diagnosed with such disorders (Desroches & Kaiman, 1964; Foss, 1994; Free et al, 1993; Gentil & Lader, 1978; Khodarahimi, 2009; Kirschner, 1999; Miller et al, 2015; Nadorff et al, 2014; Simon et al, 2016; Swart et al, 2013). In terms of the influence of anxiety disorders on dreams and dream characteristics, it might be assumed that the presence of a clinical anxiety disorder may lead to more frequent and more intense, fearful, frightening, and harming dreams, instigate anxiety-related feelings, thoughts, or emotions in dreams and may also enhance nightmare frequency, as well as increase subjective distress from nightmares.…”
mentioning
confidence: 99%
“…However, despite a relatively large body of research on dreams and nightmares in anxiety disorders, studies on the relationships between anxiety disorders and specific dream characteristics and on nightmare distress are very scarce (Rimsh & Pietrowsky, 2020; Skancke et al, 2014). The scarce existing data indicate that dreams of anxiety patients often contain different kinds of threats and dangers and various frightening, unpleasant, threatening, and negative events of high emotional intensity (Foss, 1994; Free et al, 1993; Gentil & Lader, 1978; Khodarahimi, 2009; Kirschner, 1999; Sikka et al, 2018). Investigating the emotionality of dreams of clinical patients with anxiety disorders showed that their dreams exhibit a generally lower emotional tone, more negative and sad mood and affect, higher levels of general anxiety, fright, fear, and sadness, and other negative emotions and contain various frightening, unpleasant, and negative events of high emotional intensity (Desroches & Kaiman, 1964; Free et al, 1993; Gentil & Lader, 1978).…”
mentioning
confidence: 99%
“…A large number of psychological studies indicates that dream contents are directly influenced and affected by an individual’s psychopathology (Cartwright et al, 2006; Desroches & Kaiman, 1964; Free et al, 1993; Gentil & Lader, 1978; Hartmann, 1996; Kirschner, 1999; Miller et al, 2015; Nadorff et al, 2014; Simon et al, 2016; Swart et al, 2013). According to these studies, we can assume that dreams and dream content of individuals suffering from anxiety disorders will directly reflect their mental state and be immediately associated with it.…”
mentioning
confidence: 99%
“…Although there are a number of studies that address and explore the relationships between anxiety disorders and the frequency of nightmares or bad dreams (Kellner et al, 1991; Levin & Hurvich, 1995; Nadorff et al, 2014; Nielsen et al, 2000; Ohayon et al, 1997; Picard-Deland et al, 2018; Schredl et al, 2001; Simon et al, 2016; Simonds & Parraga, 1984; Swart et al, 2013), there is still an evident lack of psychological research concerning the subject of associations between anxiety disorders and dream contents in general (Rimsh & Pietrowsky, 2020; Skancke et al, 2014). It is also necessary to note that not only are such studies scarce, the existing investigations on this particular topic bear mostly an isolated and segregated character and highlight and investigate only specific individual minor facets, aspects, and particularities of dreams and dream contents of clinical anxiety sufferers (DeCicco et al, 2013; Foss, 1994; Free et al, 1993; Gentil & Lader, 1978; Khodarahimi, 2009; Kirschner, 1999; Miller et al, 2015; Sikka et al, 2018). Anxiety disorders, however, still remain one of the most prevalent and common psychiatric disorders in the contemporary western world and become more and more widespread among European and U.S. populations each year (Remes et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation